CTIM-23. DOSE ESCALATION TRIAL OF FC-ENGINEERED ANTI-CD40 MONOCLONAL ANTIBODY (2141-V11) ADMINISTERED INTRATUMORALLY WITH D2C7-IT VIA CONVECTION-ENHANCED DELIVERY (CED) FOR RECURRENT MALIGNANT GLIOMAS (RMGS). (14th November 2022) - Desjardins, Annick; Chandramohan, Vidya; Landi, Daniel; Peters, Katherine B; Johnson, Margaret; Khasraw, Mustafa; Low, Justin; Threatt, Stevie; Bullock, Chevelle; II, James E Herndon; Lipp, Eric S; Sampson, John; et al.
Abstract: BACKGROUND: D2C7-IT, a novel immunotoxin-based cytotoxic therapy, targets epidermal growth factor receptor (EGFR) and mutant EGFR variant III. In preclinical studies, D2C7-IT kills tumor cells and prolongs survival, but is unable to generate cures in all animals. We hypothesized that immunosuppression in glioblastoma limits D2C7-IT efficacy. Eliminating glioblastoma immunosuppression via CD40 co-stimulation is anticipated to enhance D2C7-IT-induced antitumor responses. In murine glioma models, CED of D2C7-IT+αCD40 generated cures and long-term tumor-specific adaptive immunity. Hence, we are conducting a phase 1 trial of D2C7-IT+2141-V11 (αhuman-CD40) administered via CED in rMG patients. METHODS: Eligibility includes adult patients with solitary supratentorial rMG (WHO grade 3/4); ≥ 4 weeks after chemotherapy, bevacizumab, or study drug; adequate organ function; and KPS ≥ 70%. Cohorts of 3 patients are treated with increasing doses of 2141-V11 to determine the maximum tolerated dose when administered sequentially following D2C7-IT (166, 075 ng) via CED at 0.5 mL/hr. Five dose levels (DLs) are evaluated (2141-V11 at: #1: 0.70 mg; #2: 2.0 mg; #2**: 3.0 mg #2*: 4.0 mg; #3: 7.0 mg). RESULTS: As of May 29, 2022, 13 patients were treated (3 patients on DL1, DL2, and DL2**; 2 patients on DL3 and DL2*). No dose-limiting toxicities were observed; however, lower DLs were added due to higher frequency of adverse events (AEs) expected with D2C7-IT+2141-V11 with DL3 and DL2* (fever, neurologic symptoms). All patients remain alive 0.7-10.6 months after therapy. Grade ≥ 2 AEs due to D2C7-IT+2141-V11 include: headache (grade 3, n = 1; grade 2, n = 4); pyramidal tract disorder (grade 3, n = 1; grade 2, n = 2); paresthesia (grade 3, n = 1); dysphasia (grade 3, n = 1); seizures (grade 2; n = 2); fever (grade 2; n = 2); and one each of grade 2 depressed level of consciousness, fatigue, and concentration impairment. Enrollment is ongoing. CONCLUSIONS: Intratumoral administration of D2C7-IT+2141-V11 via CED is safe, encouraging efficacy results are observed.